THE CHARACTERISTIC FEATURES OF THE AUDIO-LINGUAL METHOD - Musurmonova Saodat Jamshidovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The phonetic symbols were applied within Audio-Lingual method which ensured revision, repetitions, memorizations and drills through audio media. The Audio-Lingual method develop communicative competence, quick and automatic responses of students through dialogues.